A new species of the South American genus Arthurella Albuquerque (Diptera: Muscidae), with a key to species and new records - Patitucci, Luciano D. (2011)
Fil: Patitucci, Luciano Damián. Consejo Nacional de Investigaciones Científicas y Técnicas; Buenos Aires, Argentina.